Pengaruh Pelatihan Mikroskopis Tuberkulosis Terhadap Kualitas Sediaan dan Slide Positivity Rate di Wilayah Kerja Dinas Kesehatan Kabupaten Purbalingga - Dede Kurniawan; Ning Rintiswati; Dibyo Pramono (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Introduction: Microscopic examination of sputum is a key component of the diagnosis of tuberculosis. In Purbalingga district, was conducted in 24 peripheral laboratories. Five technicians were trained in 2011-2012 and 12 technicians in 2003-2009 by National Tuberculosis Programs. Seven technicians have not trained. In 2011 slide positivity rate an average of 9.1%, 73.4% poor smear quality and 11.5% poor staining, 1.4% error rate at 34.7% laboratoriy. In 2012 slide positivity rate an average of 8.9, evenness was the highest of poor smear quality (77.7%), and 4.6% error rate at 66,7% laboratory. Therefore, need refresher training and initial training. Objective: To determine impact of training to smear quality and slide positivity rate. Methods: The research design was analytic quasi experimental with 5 days microscopic training. The research subject were 18 technician microscopic. They were divided into experimental and control group each 9 technicians with purposive sampling. The differences of smear quality and slide positivity rate were analyzed by independent t-test and Mann-Whitney test with 95% CI. Results: Training has increased the average of knowledge test score 40.7 points and average of test score the good smear quality : specimen quality increased 90 points, staining 84.4, cleanness 85.6, thickness 91.1, smear size 88.9, evenness 87.8 and increase the average of smear readings score test 22 points. The mean of smear quality and slide positivity rate of the experimental group were higher than control group. Statistical test of smear quality between eksperimental group with contol group were: specimen quality p=0.03, staining quality p=0.03, cleanness p=0.02, thickness p<0.001, size p<0.001, good evenness p<0.001, and slide positivity rate p=0.02 Conclusion: The mean of smear quality and slide positivity rate of the experimental group were higher than control group, there were significant differences of smear quality and slide positivity rate between experimental group with control group at 3 months after training.